Jerusa: The Baroque Lady - Pinheiro, Amálio (2019)
Jerusa Pires Ferreira embodied, from the small to the large, fromthe visible to the invisible, in a joyful and continuous “toing and froing,” the relationships between the hinterland and the world, the great medieval narratives and the mythopoetics of the cordel literature, the Faustian mythologies and their deviant translations in Brazil and LatinAmerica, through multiple voice and script processes contained in her “culture of borders” and in the “memory traps.” All that constitutes the Plutonic desire for assimilation described by Lezama Lima as the “Baroque Man,” and according to the levels of baroque construction procedures analyzed by Haroldo de Campos.